Program Pelita Gizi (Pendidikan Literasi Gizi) Sebagai Upaya Pencegahan Stunting Pada Bayi dan Balita Usia 0–59 Bulan di Kelurahan Sarirejo Kota Semarang - Mahmudah, Siti; Puspita, Gita Rakhma; Muna, Khafizatul; Fajriyani, Fanny Kartika (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
Stunting remains a nutritional problem among children under five in Sarirejo Village, with a prevalence of 5.56% in 2025. This community service program aimed to improve nutrition literacy and prevent stunting through the "Pelita Gizi" program, which employed creative educational approaches. The methods included nutrition education using animated videos, demonstrations of "Isi Piringku" (balanced plate), and an educational game "Susun Isi Piringku". The activity involved 12 mothers of toddlers selected through purposive sampling in RW 08 Sarirejo. Evaluation was carried out through pre-test and post-test, as well as monitoring the application of balanced nutrition practices at home. The results showed an increase in participants' knowledge, with average post-test scores rising from 83% to 93%. One-week monitoring also indicated positive changes in children's dietary practices. The educational media were well received and considered easier to understand than conventional counseling. The "Pelita Gizi" program proved effective in improving nutrition literacy and has the potential to be replicated as a creative community nutrition education model